Hepcidin - A novel biomarker with changing trends - Kali, Arunava; Charles, Marie Victor Pravin; Seetharam, Rathan Shetty Kolkebail (Pharmacognosy Reviews)
Hepcidin is a novel peptide hormone of hepatic origin. It has a crucial role in iron metabolism. The causative association of this peptide in anemia and iron overloading states has been well established. Current research has expanded the diagnostic implications of hepcidin in other medical conditions. Increased serum hepcidin has been reported in neoplastic diseases, inflammation, and sepsis. However, the clinical use of hepcidin as a biomarker is limited owing to nonavailability of an appropriate diagnostic test. Assays for serum and urine hepcidin estimation have been developed recently, which are likely to facilitate the use of hepcidin in research as well as in patient care in the near future.
Keywords: Biomarker; hepcidin; iron metabolism; malignancy; sepsis